ChemInform Abstract: A General and Regioselective Synthesis of 5‐Trifluoromethyl‐pyrazoles. Issue 3 (22nd January 2013) - Foster, Robert S.; Jakobi, Harald; Harrity, Joseph P. A.
Abstract Sydnones (III) are prepared by two approaches as precursors for the cycloaddition reaction with terminal or internal alkynes to give the pyrazoles.